PENERAPAN MATEMATIKA DALAM ILMU EKONOMI FUNGSI PERMINTAAN DAN PENAWARAN - Hoirunnisa, Adinda; Mappi, Dinda Refani; Firmansyah, Muhammad Rafi; Innalexsyah, Nakeisha Annora; Mazidah, Nurul; Akbar, Reza Maulana (JITAA : Journal Of International Taxation, Accounting And Auditing, 2024)
Economic mathematics is an approach or method of solving economic problems using mathematical symbols and mathematical logic. Economists also often use mathematics in solving economic problems, one of which is function material. Therefore, this study aims to examine the application of mathematics in economics: demand and supply functions as support and reference in learning activities. The method used in the research uses the literature study method. The results showed that the main factors that affect demand include the price of goods, consumer income, prices of other goods, expectations of future prices, consumer tastes, and advertising spending. The law of demand states that if the price of goods rises, demand tends to fall, and vice versa. Supply refers to the relationship between the price of a good and the quantity of the good that producers offer. The main factors that affect supply include the price of the product, the level of technology, the price of production factors, the price of other related goods, and the producer's expectations of future prices.